Determination of Heavy Metals in Irrigation Water, Soil, Paddy, and Produced Rice of Some Paddy Fields of Iraq - Chyad, Alaa A.; Saeed, Ahmed M.; Alhendi, Abeer S. (Iraqi Journal of Science, 2022)
Iraq is a developing country with a high population. In Iraq, heavy metal and metalloid contamination has resulted from both industrialisation and environmental sources, providing serious health risks to the local population. We conducted one of the most comprehensive analyses on the current state of Iraq’s heavy metal and metalloid pollution in this paper, which included water, soil, paddy, and rice. A study was carried out to determine the concentration of heavy metals including Lead (Pb), Cadmium (Cd), Iron (Fe), manganese (Mn), Cobalt (Co), Magnesium (Mg), Aluminum (Al), and Copper (Cu) of 39 irrigation water samples, 75 soil samples, 75 paddy samples, and 75 rice samples in two Iraqi governorates (Diyala , and Salah al-Din ). Samples were taken from three fields in each province.. Atomic Absorption Spectrophotometer was used to determine heavy metals concentrations. Iraqi Quality Standardization (IQS (and World Health Organization (WHO) were considered as the permissible limits. The results showed that all irrigation water samples were exceeded the permissible limit for Pb, Cd, Fe, and Mn metals, while all soil samples were exceeded for Mn and Mg metals. Paddy and rice samples were exceeded for only Pb metal permissible limit, which was high, for example, Pb metal concentrations of rice and paddy ranged from 1.805-4.776 mg/kg, 0.642-3.481 mg/kg respectively, while the permissible limit was 0.2 mg/kg. Consequently, rice samples were deemed unfit for human consumption, with the contamination coming from irrigation water. therefore, this paper has suggested that the Irrigation water treatment should be strongly advised and evaluated.